Code switching found in cinta laura’s video on her instagram tv - Wiraputri, Ni Made Dwi Yanti; Sulatra, I Komang; Putra, I GB Wahyu Nugraha (Journal of Language and Applied Linguistics, 2021)
This study concerns with the code switching found in Cinta Laura's video on her Instagram TV. Descriptive qualitative method is used for analyzing the data from ten videos. This study used the theory proposed by Poplack (1980) about types of code switching and the theory from Hoffman (1991) about the reasons of code switching. This study shows that there are three types of code switching found and six reasons of code switching found. The result of this study shows that intra-sentential switching is the most frequently used in types of code switching and particular topic is the most frequently used in the reasons of code switching. The phenomenon of code switching occurs in many media such as social media. By doing code switching, it is easier to build a sense of solidarity rather than using only one language. Therefore, code switching is an interesting topic to discuss in sociolinguistics research.